LINGUISTIC POLITENESS STRATEGY OF PRESIDENT BOLA AHMED TINUBU'S INAUGURAL SPEECH OF MAY 29, 2023 - OGUNDEJI , Awoniyi Olaleken (International Journal of Arts, Languages, Linguistics and Literary Studies, 2024)
The Language analysts have examined various presidential inaugural speeches from a number of language levels: syntax, stylistics, pragmatics, sociolinguistics, and discourse. However, the linguists have paid little or no attention to the linguistic politeness strategies of President Bola Ahmed Tinubu's Inaugural Speech of May 29, 2023 using linguistic maxims' theory of Leech. Therefore, there exists a wide lacuna in language studies and literature. To narrow the vacuum, this study is aimed at identifying the linguistic politeness strategies deployed by President Bola Ahmed Tinubu (PBAT) on May 29, 2023. The research obtains data from the widely circulated inaugural speech of the Nigerian president as published by The Nation, a widely read Nigerian Newspaper. The study employs Leech's theory of politeness to outline the linguistic politeness strategies PBAT applied in presenting himself as intelligible, accommodative and godsent president of Nigeria. The study reveals that PBAT applied tact maxim, approbation maxim, generosity maxim, modesty maxim, agreement maxim, and sympathy maxim to convince Nigerians over his ability to deliver on polite governance with strict adherence to rule of laws. The study therefore recommends that public figures should equip themselves with politeness tacts in order to be admired speakers and acceptable leaders in the society.